Cell cycle and differentiation of Sca-1+ and Sca-1- hematopoietic stem and progenitor cells - Páral, Petr; Faltusová, Kateřina; Molík, Martin; Renešová, Nicol; Šefc, Luděk; Nečas, Emanuel (Cell Cycle, 2018)
Hematopoietic stem and progenitor cells (HSPCs) are crucial for lifelong blood cell production. We analyzed the cell cycle and cell production rate in HSPCs in murine hematopoiesis. The labeling of DNA-synthesizing cells by two thymidine analogues, optimized for in-vivo use, enabled determination of the cell cycle flow rate into G2-phase, the duration of S-phase and the average cell cycle time in Sca-1+ and Sca-1- HSPCs. Determination of cells with 2n DNA content labeled in preceding S-phase was then used to establish the cell flow rates in G1-phase. Our measurements revealed a significant difference in how Sca-1+ and Sca-1- myeloid progenitors self-renew and differentiate. Division of the Sca-1+ progenitors led to loss of the Sca-1 marker in about half of newly produced cells, corresponding to asymmetric cell division. Sca-1- cells arising from cell division entered a new round of the cell cycle, corresponding to symmetric self-renewing cell division. The novel data also enabled the estimation of the cell production rates in Sca-1+ and in three subtypes of Sca-1- HSPCs and revealed Sca-1 negative cells as the major amplification stage in the blood cell development.
Keywords: Male; zvířata; proliferace buněk; buněčná sebeobnova; hematopoetické kmenové buňky; membránové proteiny; počet buněk; Animals; DNA; Cell Proliferation; Cell Differentiation; Cell Cycle; ženské pohlaví; buněčná diferenciace; Hematopoietic Stem Cells; Cell Count; G2 fáze; Mice, Inbred C57BL; antigeny Ly; Membrane Proteins; Rheology; S Phase; Cell Self Renewal; Female; Antigens, Ly; G2 Phase; mužské pohlaví; S fáze; buněčný cyklus; myši inbrední C57BL; reologie